Close Contact with Patients and Immunity Status as Major Risk Factors for Leprosy Among Adults - Puji Utami; Titi Indriyati; Sumiati Bedah (FORIKES, 2026)
Leprosy is a chronic infectious disease caused by Mycobacterium leprae that affects peripheral nerves, skin, the upper respiratory tract, eyes, and nasal mucosa. Despite global progress, it remains a public health problem in Indonesia. This study aimed to analyze the risk factors associated with leprosy among adults at UPT RSUD RAA Soewondo Pati in 2025. An analytical observational study with a case–control design was conducted involving 70 cases and 70 controls (1:1 ratio). Data were analyzed using Chi‑square tests and multivariate logistic regression. In results, age (p=0.007), sex (p=0.033), close contact with leprosy patients (p=0.005), personal hygiene (p=0.011), and immunity status (p=0.000) were significantly associated with leprosy. Multivariate analysis identified close contact with leprosy patients (OR=8.3; 95% CI: 1.897–36.310) and immunity status (OR=6.2; 95% CI: 2.798–13.570) as the strongest predictors. In conclusion, close contact with leprosy patients and compromised immunity status are the major risk factors for leprosy among adults. Strengthening early detection, monitoring close contacts, improving personal hygiene, and enhancing community immunity are essential strategies to reduce transmission and prevent new cases.Keywords: leprosy; risk factors; close contact